Seeking to enhance the bioenergy of municipal sludge: Effect of alkali pre-treatment and soluble organic matter supplementation. (October 2017) - Zahedi, S.; Rivero, M.; Solera, R.; Perez, M.
Highlights: Bioenergy of municipal waste has been studied. Glycerine addition (GA) improved the methane production (MP). GA not affected the pH sludge and organic matter content of the effluent. GA not affected the stability of the reactor: ratio volatile fatty acid/Alkalinity was <0.4. Alkali pre-treatment improved the sludge biodegradability. Abstract: The aim of this research is to enhance the mesophilic anaerobic digestion of municipal sludge from Cadiz-San Fernando (Spain) wastewater treatment plant at 20 days hydraulic retention time (HRT). Two different strategies were tested to improve the process: co-digestion with the addition of soluble organic matter (1% v/v); and alkali sludge pre-treatment (NaOH) prior to co-digestion with glycerine (1% v/v). Methane production (MP) was substantially enhanced (from 0.36 ± 0.09 L CH4 l/d to 0.85 ± 0.16 L CH4 l/d), as was specific methane production (SMP) (from 0.20 ± 0.05 L CH4 /g VS to 0.49 ± 0.09 L CH4 /g VS) when glycerine was added. The addition of glycerine does not seem to affect sludge stability, the quality of the effluent in terms of pH and organic matter content, i.e. volatile fatty acids (VFA), soluble organic matter and total volatile solid, or process stability (VFA/Alkalinity ratio < 0.4). Alkali pre-treatment prior to co-digestion resulted in a high increase in soluble organic loading rates (more than 20%) and acidification yield (more than 50%). At 20 days HRT, however, it led to overload of the system and total destabilization of the mesophilic anaerobic co-digestion of sewage sludge and glycerine.